A optimised method for quantifying glenoid orientation - Amadi,HO; Banerjee,S; Hansen,UN; Wallace,AL; Bull,AMJ (International Journal of Shoulder Surgery, 2008)
A robust quantification method is essential for inter-subject glenoid comparison and planning of total shoulder arthroplasty. This study compared various scapular and glenoid axes with each other in order to optimally define the most appropriate method of quantifying glenoid version and inclination.Six glenoid and eight scapular axes were defined and quantified from identifiable landmarks of twenty-one scapular image scans. Pathology independency and insensitivity of each axis to inter-subject morphological variation within its region was tested. Glenoid version and inclination were calculated using the best axes from the two regions.The best glenoid axis was the normal to a least-square plane fit on the glenoid rim, directed approximately medio-laterally. The best scapular axis was the normal to a plane formed by the spine root and lateral border ridge. Glenoid inclination was 15.7° ± 5.1° superiorly and version was 4.9° ± 6.1°, retroversion.The choice of axes in the present technique makes it insensitive to pathology and scapular morphological variabilities. Its application would effectively improve inter-subject glenoid version comparison, surgical planning and design of prostheses for shoulder arthroplasty.